Construction methods and latest applications of kidney cancer organoids - Zhiqiang Li; Yanqiu You; Bingzheng Feng; Jibing Chen; Hongjun Gao; Fujun Li; Fujun Li (Frontiers Media S.A., 2024)
Renal cell carcinoma (RCC) is one of the deadliest malignant tumors. Despite significant advances in RCC treatment over the past decade, complete remission is rarely achieved. Consequently, there is an urgent need to explore and develop new therapies to improve the survival rates and quality of life for patients. In recent years, the development of tumor organoid technology has attracted widespread attention as it can more accurately simulate the spatial structure and physiological characteristics of tumors within the human body. In this review, we summarize the main methods currently used to construct kidney cancer organoids, as well as their various biological and clinical applications. Furthermore, combining organoids with other technologies, such as co-culture techniques and microfluidic technologies, can further develop organoids and address their limitations, creating more practical models. This approach summarizes the interactions between different tissues or organs during tumor progression. Finally, we also provide an outlook on the construction and application of kidney cancer organoids. These rapidly evolving kidney cancer organoids may soon become a focal point in the development of in vitro clinical models and therapeutic research for kidney cancer.